Influence of Sunflower Seed Husks Ash on the Structure Formation and Properties of Cement Concrete - Evgenii M. Shcherban'; Sergey A. Stel'makh; Alexey N. Beskopylny; Levon R. Mailyan; Besarion Meskhi; Andrei Chernil’nik; Diana El'shaeva; Anastasia Pogrebnyak; Roman Yaschenko (Salehan Institute of Higher Education, 2024)
The limitation of the application of non-renewable materials is one of the solutions to the problem of the sustainable evolution of civilization in the 21st century. Using additional binders in concrete obtained from plant waste will be economically and environmentally beneficial and will also allow us to move closer to achieving sustainable development goals. This study searches for rational composition components and a methodological approach regarding the technological characteristics to get the highest quality elements and prime concrete properties on the basis of sunflower seed husk ash (SSHA). Experimental concrete specimens were manufactured with partial Portland cement substitution with SSHA amounts ranging from 2% to 16% by weight in increments of 2%. This study focuses on investigating the density and workability of the concrete mixture, along with the compressive strength, concrete density, and water absorption. This article used granulometric, microscopic, and X-ray phase analysis methods. Including SSHA in all considered ranges reduces the slump in concrete mixtures. The optimal SSHA content in concrete is up to 12%. An 8% SSHA content has been found to deliver the most favorable mechanical characteristics of the concrete studied. The compressive strength of the investigated concrete has increased by 14.89%, and water absorption has decreased by 15.78%. Doi: 10.28991/CEJ-2024-010-05-08 Full Text: PDF